Pengaruh Motivasi terhadap Peningkatan Kinerja Pegawai Di Biro Administrasi Pembangunan - Armansyah Armansyah; Selvia Andita; Muhammad Isa Alamsyahbana; Yuritanto Yuritanto; Herman Herman; Eko Murti Saputra (Universitas Batanghari Jambi, 2023)
This study examines the effect of motivation on performance improvement at the Riau Archipelago Development Administration Agency. This type of quantitative research is used in this study. The analytical technique used to determine the impact of motivation on performance is to analyze the data and apply the results to the entire population. In addition, it is necessary to conduct a study using classical assumption instruments and analysis to find out whether the assumptions made in this study are correct or not. In addition, simple linear regression analysis and hypothesis testing can be used to determine whether there is a correlation between variables. The results of the linear regression test give the regression equation Y = 14.009 + 0.863X1 e, where these results indicate that for each unit of increased motivation, morale increases by 0.863 and has a positive impact. Based on the research results it is known that the value of motivation is 7.924. This value is greater than the value of 2.021 which is the limit of tcount, meaning that motivation partially has a significant impact on the performance of employees of the Riau Islands Development Administration Agency. Based on the results of the analysis, the R-squared value is 0.623. The magnitude of the impact of motivational variables on performance is 62.3%, while the remaining 37.7% is influenced by other factors.